Integration of the Merdeka Curriculum and Islamic Education in Developing Elementary School Students’ Character - Iwan Satria; Feri Riski Dinata (Bulletin of Indonesian Islamic Studies, 2025)
This study examines the integration of the Merdeka Curriculum with Islamic educational values at UPT SD Negeri 02 Serdang Kuring. Addressing the limited scholarly attention on Islamic-values integration at the primary-school level, this research employs a qualitative descriptive design using observation, interviews, and documentation analyzed through the Miles and Huberman model. The findings reveal that integration is implemented systematically through instructional planning, teacher modeling, student habituation, reinforcement of a religious school culture, and collaboration between teachers, school leaders, and parents, supported by the use of local wisdom as contextual grounding. This integration strengthens students’ character formation, particularly responsibility, honesty, discipline, and hard work, aligning with the Profile of Pancasila Students. The study’s novelty lies in identifying a collaborative, context-based integration pattern as an effective character education strategy. The results suggest the need for adaptable Islamic-values-based character education models within the Merdeka Curriculum for wider application in diverse school contexts.